THE INFLUENCE OF SOCIAL MEDIA MARKETING AND CORPORATE IMAGE ON PURCHASE INTENTION OF MS GLOW PRODUCTS IN THE PERSPECTIVE OF ISLAMIC MARKETING - Sri Kinanti, Anggiani; Setiawan, Agus; Choirudin; Ligery, Finny (Jurnal Dinamika Ekonomi Syariah, 2025)
This research aims to analyze the influence of social media marketing and company image on purchase intentions for Ms Glow products in Tulang Bawang Regency from an Islamic marketing perspective. With the development of the digital era, social media has become an effective tool in marketing strategies, company image has become a reference for general assessments regarding purchasing intentions for Ms Glow products. In the beauty industry. However, from an Islamic marketing perspective, the principles of ethics, honesty and justice must still be upheld. This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to customers of the MS Glow clinic in Tulang Bawang. Data analysis was carried out using the multiple linear regression method to examine the relationship between social media marketing, company image on purchase intentions, and customer purchasing decisions within the Islamic marketing frame. The research results show that social media marketing has a significant influence on customer purchasing decisions, while company image also has an important role in purchasing intentions and building consumer trust. In an Islamic marketing perspective, transparency in promotions, halal products, and conformity with sharia values ​​are factors that influence customer decisions. Therefore, implementing marketing strategies that are in accordance with Islamic principles can increase customer loyalty and satisfaction.